Education has a significant effect on the performance of implementing nurses in hospitals - Gustini Gustini; Lamaria Situmeang; Syaharuddin Syaharuddin; Prasetyowati Prasetyowati; Suprapto Suprapto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Higher education typically gives nurses a more profound knowledge of healthcare practices and recent developments and enhances nurses' analytical and problem-solving abilities, enabling them to provide more effective care. Aim: Knowing education significantly affects the performance of implementing nurses in hospitals. Methods: The research design is qualitative analytical descriptive research with a cross-sectional approach. The population is all nurses working in the internal care room, and as many as 50 responses using the sampling technique are total sampling. Results: Showing the chi-square test with the level of meaning (α) = 0.05, obtained p value = 0.003, education significantly influences the implementing nurse's performance. Conclusion: Education significantly influences the performance of implementing nurses, and continuing education can be an effective strategy for improving the standard of health care in hospitals. Nurses with higher education tend to have better clinical knowledge and skills, enabling them to provide higher-quality care.